2023
DOI: 10.1037/cap0000369
|View full text |Cite
|
Sign up to set email alerts
|

Towards high standards of evidence for cognitive behaviour therapy for perfectionism: A critique of Smith et al. (2023).

Sarah J. Egan,
Tracey D. Wade,
Hunna J. Watson
et al.

Abstract: Perfectionism is associated with symptoms of multiple psychological disorders. In this commentary, we outline our numerous concerns regarding a recent meta-analysis by Smith et al. (2023) that examined the efficacy of cognitive behaviour therapy for perfectionism (CBT-P). To ensure health care and policy decisions are based on high-quality evidence, evidence summaries need to be held to high standards of accountability. The study did not systematically search the literature, and omitted previous studies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…It is vital to be transparent and clear about empirically valid findings in treatment research to safeguard patients, provide guidance for policymakers, and facilitate the expansion of empirical knowledge. In the current article, we address the criticisms and allegations in Egan et al’s (2023) critique of our meta-analytic replication (Smith et al, 2023) that assessed the efficacy of cognitive behavioural therapy for perfectionism (CBT-P). By reanalyzing data from 16 randomized controlled trials included in three meta-analytic reviews, we confirmed some limited support for CBT-P while highlighting that many participants do not experience reliable or sustained posttreatment improvements.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is vital to be transparent and clear about empirically valid findings in treatment research to safeguard patients, provide guidance for policymakers, and facilitate the expansion of empirical knowledge. In the current article, we address the criticisms and allegations in Egan et al’s (2023) critique of our meta-analytic replication (Smith et al, 2023) that assessed the efficacy of cognitive behavioural therapy for perfectionism (CBT-P). By reanalyzing data from 16 randomized controlled trials included in three meta-analytic reviews, we confirmed some limited support for CBT-P while highlighting that many participants do not experience reliable or sustained posttreatment improvements.…”
mentioning
confidence: 99%
“…Further, we found a lack of evidence of change in several pernicious elements of perfectionism and that the dropout rate was higher in treatment conditions than in control conditions, suggesting poor acceptability. In this rejoinder, we respond to Egan et al (2023) and discuss what is needed to improve the quality of research and advance treatments for perfectionism. We underscore the ongoing necessity for continuous improvements and new developments that transcend existing paradigms and pave the way for more effective treatment strategies for people struggling with perfectionism.…”
mentioning
confidence: 99%
See 3 more Smart Citations